Recovery-Associated Resting-State Activity and Connectivity Alterations in Anorexia Nervosa - Lotter, Leon D.; von Polier, Georg; Offermann, Jan; Buettgen, Kimberly; Stanetzky, Lukas; Eickhoff, Simon B.; Konrad, Kerstin; Seitz, Jochen; Dukart, Juergen (Biological psychiatry : cognitive neuroscience and neuroimaging, 2021)
Previous studies provided controversial insight on the impact of starvation, disease status, and underlying gray matter volume (GMV) changes on resting-state functional magnetic resonance imaging alterations in anorexia nervosa (AN). Here, we adapt a combined longitudinal and cross-sectional approach to disentangle the effects of these factors on resting-state alterations in AN. Overall, 87 female subjects were included in the study: adolescent patients with acute AN scanned at inpatient admission (n = 22, mean age 15.3 years) and at discharge (n = 21), patients who recovered from AN (n = 21, mean age 22.3 years), and two groups of healthy age-matched control subjects (both n = 22, mean age 16.0 and 22.5 years, respectively). Whole-brain measures of resting-state activity and functional connectivity were computed (network-based statistics, global correlation, integrated local correlation, and fractional amplitude of low-frequency fluctuations) to assess resting-state functional magnetic resonance imaging alterations over the course of AN treatment before and after controlling for underlying GMV. Patients with acute AN displayed strong and widespread prefrontal, sensorimotor, parietal, temporal, precuneal, and insular reductions of resting-state connectivity and activity. All alterations were independent of GMV and were largely normalized in short-term recovered AN and absent in long-term recovered patients. Resting-state functional magnetic resonance imaging alterations in AN constitute acute and GMV-independent, presumably starvation-related, phenomena. The majority of alterations found here normalized over the course of recovery without evidence for possible preexisting trait- or remaining “scar” effects.